2020
DOI: 10.1038/s41598-020-65087-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes of the Pho regulon is altered in Streptomyces coelicolor

Abstract: Most currently used antibiotics originate from Streptomycetes and phosphate limitation is an important trigger of their biosynthesis. Understanding the molecular processes underpinning such regulation is of crucial importance to exploit the great metabolic diversity of these bacteria and get a better understanding of the role of these molecules in the physiology of the producing bacteria. To contribute to this field, a comparative proteomic analysis of two closely related model strains, Streptomyces lividans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 119 publications
2
66
0
Order By: Relevance
“…This response is controlled by the two-component system PhoR/PhoP, which is able to induce the high-affinity phosphate transport system, phosphatases, down-regulation of phosphate consuming processes and upregulation of genes involving phosphate mediated reactions [ 53 , 54 ]. In phosphate limited conditions, the homeostatic processes triggered to compensate the ATP deficit, lead to a strong activation of the oxidative and amino acids metabolism, resulting in abundant generation of reduced cofactors and ATP, favoring the antibiotic synthesis as a feasible mechanism to adjust the ATP generation to low phosphate availability [ 55 , 56 ]. Additionally, penicillin and cephalosporin antibiotics induce an ATP-consuming futile cycle of polymerization/degradation of the cell wall, regulating the ATP levels and phosphate content [ 52 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…This response is controlled by the two-component system PhoR/PhoP, which is able to induce the high-affinity phosphate transport system, phosphatases, down-regulation of phosphate consuming processes and upregulation of genes involving phosphate mediated reactions [ 53 , 54 ]. In phosphate limited conditions, the homeostatic processes triggered to compensate the ATP deficit, lead to a strong activation of the oxidative and amino acids metabolism, resulting in abundant generation of reduced cofactors and ATP, favoring the antibiotic synthesis as a feasible mechanism to adjust the ATP generation to low phosphate availability [ 55 , 56 ]. Additionally, penicillin and cephalosporin antibiotics induce an ATP-consuming futile cycle of polymerization/degradation of the cell wall, regulating the ATP levels and phosphate content [ 52 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…It also revealed that some strains have far lower lipid content on glucose than on glycerol ( Figure 1b). These strains might have, like S. coelicolor, an oxidative metabolism yielding an insufficient amount of glycerol3P to support high lipid biosynthesis on glucose [9]. Thirty and fifteen strains (forty-five strains) had a medium (50-100 µg/mg) or high (>100 µg/mg) lipid content on glycerol whereas only twenty and seven strains (twenty-seven strains) had medium or high lipid content on glucose, respectively.…”
Section: The Lipid Content and Antibiotic Activity Of The Streptomycementioning
confidence: 99%
“…S. coelicolor suffers energetic stress since the two component system PhoR/PhoP that positively controls the phosphate supply, necessary for ATP synthesis, is weakly expressed in this strain [9] whereas the ppk mutant suffers energetic stress since its lacks PPK, an important enzyme that regenerates ATP from ADP and polyphosphate [10,11]. In these two strains, similar homeostatic processes are triggered to restore their energetic balance [7,9]. Such processes include the activation of their TCA cycle, which yields reduced co-factors whose re-oxidation by the respiratory chain generates ATP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA biosynthesis is induced during phosphate limited conditions; recently it has been proposed that CA production may be a consequence of a homeostatic response aimed to compensate for the ATP deficit under phosphate depletion [ 19 ]. This mechanism would trigger a strong activation of oxidative and amino acid metabolism, producing reduced cofactors and ATP and favoring the antibiotic biosynthesis as a feasible mechanism to adjust the ATP generation [ 20 , 21 ]. Moreover, the simultaneous secretion of penicillin and cephalosporins antibiotics along with β-lactamase enzymes and β-lactamase inhibitors would tightly control the energetic impact of an ATP-consuming futile cycle of polymerization/degradation of the cell wall caused by the β-lactam antibiotics accumulation [ 19 , 22 , 23 ].…”
Section: Overview Of Ca Biosynthesis In S Clavuligerus mentioning
confidence: 99%